Optimizing the Delivery of Multiple Ecosystem Goods and Services in Agricultural Systems - Evangelia G. Drakou (Frontiers Research Topics, 2017)
Agricultural land is subjected to a variety of societal pressures, as demands for food, animal feed, and biomass production increase, with an added requirement to simultaneously maintain natural areas and mitigate climatic and environmental impacts. The biotic elements of agricultural systems interact with the abiotic environment to generate a number of ecosystem functions that offer services benefiting humans across many scales of time and space. The intensification of agriculture generally reduces biodiversity including that within soil, and impacts negatively upon a number of regulating and supporting ecosystem services. There is a global need toward achieving sustainable agricultural systems, as also highlighted in the United Nations Sustainable Development Goals. There is hence a need for management regimes that enhance both agricultural production and the associated provision of multiple ecosystem services. The articles of this Research Topic enhance our knowledge of how management practices applied to agricultural systems affect the delivery of multiple ecosystem services and how trade-offs between provisioning, regulating, and supporting services can be handled both above- and below-ground. They also show the diversity of topics that need to be considered within the framework of ecosystem services delivered by agricultural systems, from knowledge on basic concepts and newly-proposed frameworks, to a focus on specific ecosystem types such as grasslands and high nature-value farmlands, pollinator habitats, and soil habitats. This diversity of topics indicates the need for broader-scope research, integrated with targeted scientific research to promote sustainable agricultural practices and to ensure food security.